2012
DOI: 10.1159/000337029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Body Site on Adult Female Skin Surface pH

Abstract: Background: pH is known as an important parameter in epidermal barrier function and homeostasis. Aim: The impact of age and body site on skin surface pH (pHSS) of women was evaluated in vivo. Methods: Time domain dual lifetime referencing with luminescent sensor foils was used for pHSS measurements. pHSS was measured on the forehead, the temple, and the volar forearm of adult females (n = 97, 52.87 ± 18.58 years, 20–97 years). Every single measurement contained 2,500 pH values … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 65 publications
2
39
0
Order By: Relevance
“…In moderately aged (50 to 80 years) individuals, abnormal stratum corneum acidification results in delayed lipid processing, delayed permeability barrier recovery, and abnormal stratum corneum integrity, ion transport and turnover. [40][41][42][43] Flattening of the dermo-epidermal junction at sites that were highly corrugated in youth is the most consistent change found in aged skin 44 and is due primarily to a retraction of the rete ridges. 30 This reduced interdigitation between epidermis and dermis results is less resistance to shearing forces 13,22 as well as a reduced supply of nutrients and oxygen.…”
Section: Epidermismentioning
confidence: 99%
“…In moderately aged (50 to 80 years) individuals, abnormal stratum corneum acidification results in delayed lipid processing, delayed permeability barrier recovery, and abnormal stratum corneum integrity, ion transport and turnover. [40][41][42][43] Flattening of the dermo-epidermal junction at sites that were highly corrugated in youth is the most consistent change found in aged skin 44 and is due primarily to a retraction of the rete ridges. 30 This reduced interdigitation between epidermis and dermis results is less resistance to shearing forces 13,22 as well as a reduced supply of nutrients and oxygen.…”
Section: Epidermismentioning
confidence: 99%
“…In postmenopausal compared with premenopausal woman the pH increased from 4.7 to 5.0. Well documented are an increased SC pH and a reduced buffer capacity in the elderly …”
Section: Ph Of the Healthy Skinmentioning
confidence: 99%
“…The values measured on the untreated forearm serve as general baseline values for the respective study subjects as we did not measure baseline values on both arms before the start of the application period. In the literature [29,30,31,32] as well as in our own first experiment, we found that there is no significant difference between the baseline pH ss of different body sites, which is why we did not carry out further measurements.…”
Section: Discussionmentioning
confidence: 88%